OC-089 Transient hiatus hernia during transient lower oesophageal sphincter relaxations. (28th May 2012) - Lee, Y Y; Whiting, J R H; Robertson, E V; Derakhshan, M H; Wirz, A A; Kelman, A; Morrison, D; Connolly, P; McColl, K E L
Abstract : Introduction: In hiatus hernia there is proximal displacement of the gastro-oesophageal junction (GOJ) relative to the crural diaphragm impairing barrier function. Fluoroscopic studies have indicated proximal migration of the GOJ during TLOSRs but detailed study has been limited by radiation exposure. Using a non-radiological technique we have performed detailed examination of the GOJ during TLOSRs in healthy volunteers. Methods: In twelve subjects, a small magnet (2×1 mm) was endoscopically clipped to the GOJ and the combined assembly of Hall Effect probe and 36 channel high resolution manometer (Sierra Scientific Inc., USA) was passed nasally. After a 600-calorie test meal (Fortisip, Nurticia, UK), the subjects were studied for 90 min. Results: There was a median of 5 TLOSRs from each of the 12 volunteers. The median (range) amplitude and duration of GOJ migration from start to end of TLOSRs was 4.34 cm (1.6–8.8) and 23.63s (11.3–41.6) respectively. The proximal migration of GOJ during a TLOSR was characterised by a slow start (phase A) before accelerating (phase B) to peak amplitude. Descent of GOJ started off quickly (phase C) before slowing down (phase D) to baseline. These four different phases of movement are confirmed using mathematical modelling. The polynomial equation (1) and its differential (2) allow the calculation of maximum rate achievable for the four different phases using Microsoft Excel 2010 software: (1) y = ax 6 + bx 5 + cx 4 + dx 3 + ex 2 + fx (2) dy/dx = 6 ax 5 + 5 bx 4 + 4 cx 3 + 3 dx 2 + 2 ex + f where y is amplitude (cm), dy/dx is the differential of y, x is time (s) and a to f are non-linear regression constants. The median (range) velocity of phase C was 0.92 cm/s (0.33–2.35) and this was faster when compared to phase B 0.67 cm/s (0.23–1.73), phase D 0.36 cm/s (0.06–0.99) and phase A 0.30 cm/s (0.03–2.31) respectively; p<0.0001. Phase C velocity was strongly correlated with amplitude of GOJ migration with a correlation coefficient of 0.84 (p=0.0001) but not the other three phases. None of the phases correlated with duration of GOJ migration during TLOSRs. Conclusion: The marked proximal movement of GOJ during TLOSRs represents transient and very severe herniation of the GOJ. Our study also suggests that the initial return of the GOJ to the diaphragmatic hiatus following TLOSRs may be controlled by elastic recoil of the phreno-oesophageal ligament. Competing interests: None declared.